АЛГОРИТМИ ФУНКЦІОНУВАННЯ ТА ПРОГРАМНЕ ЗАБЕЗПЕЧЕННЯ БАГАТОРІВНЕВОЇ СИСТЕМИ МОНІТОРИНГУ СТАНУ ТА ТЕХНІЧНОГО ДІАГНОСТУВАННЯ ОБЛАДНАННЯ ОБ’ЄКТІВ ЕЛЕКТРОЕНЕРГЕТИКИ - Мислович, М.В.; Сисак, Р.М.; Остапчук, Л.Б.; Гижко, Ю.І.; Герцик, С.М. (Інститут електродинаміки НАН України, Київ, 2016)
Algorithms and software of multilevel system for remote monitoring and diagnostics of electrical power facilities equipment are discussed. The system enables adaptation to the structure of a particular object, as well as deep diagnosing of such equipment, and has low cost and high efficiency, which is achieved by distributing of computing resources and diagnostic functions between modules of the diagnostic systems that operate at different levels of the hierarchy, as well as by implementation of bidirectional exchange of diagnostic information between those modules taking into account the severity of defects. References 3.